A question of Jackson Pollock’s balance: using lacunarity and fractal analysis to distinguish poured paintings by adults and children - Fairbanks, M. S.; Viengkham, C.; Andersson, A.; Baldwin, D.; Spehar, B.; Mureika, J. R.; Taylor, R. P. (Frontiers in Physics, 2025)
We investigate the artistic patterns generated by the pouring technique made famous by Jackson Pollock. To determine if poured patterns can be distinguished based on the artist age, we apply computer analysis techniques to paintings created under controlled conditions by children (four to six years old) and adults (18–25 years old) pouring fluid paint onto horizontal sheets of paper. Both groups of art display a high visual complexity due to the multi-scaled paint structure generated by the pouring process. However, the two groups demonstrate statistically significant differences when this structure is quantified using both multifractal and lacunarity analysis. Whereas the multifractal analysis probes the scaling characteristics of the patterns, lacunarity quantifies clustering in their spatial distributions. We find that the children’s paintings are characterized by smaller fractal dimensions (indicating a reduced contribution of fine structure) and by larger lacunarity parameters (indicating a larger clustering of this fine structure) compared to the adult paintings. We compare these results to those of two famous poured works by Jackson Pollock and Max Ernst as a preliminary step to investigating the potential origins of the fractal and lacunarity variations across artists, which includes motions related to biomechanical balance. Finally, to examine the impact on audiences, we ask observers to rate their perceptions of the paintings. These ratings indicate a rise in interest and pleasantness for paintings with lower fractal dimensions and larger lacunarity.